1967
DOI: 10.1029/jz072i012p03075
|View full text |Cite
|
Sign up to set email alerts
|

Response of well-aquifer systems to Earth tides

Abstract: The water level in a well open to an artesian aquifer responds to pressure‐head fluctuations caused by the dilatation of the aquifer. Based on hydrologic considerations, it is shown that (1) most well‐aquifer systems respond to disturbances with periods of less than several days as if the well were drilled into a medium of infinite or partially bounded extent, and (2) the representation of an aquifer as a finite cavity is unrealistic for most well‐aquifer systems. The amplitude of tidal water level fluctuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
332
0
12

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(345 citation statements)
references
References 13 publications
1
332
0
12
Order By: Relevance
“…La marea terrestre actúa directamente sobre la matriz de los materiales que conforman el acuífero, por lo que la respuesta del nivel del agua dentro de un pozo a la acción de la marea terrestre es controlada principalmente por las propiedades elásticas de la matriz porosa; mientras que, la presión barométrica actúa en la superficie libre del agua dentro del pozo y en la superficie del terreno de manera simultánea (Bredehoeft, 1967;Van Der Kamp y Gale, 1983;Rojstaczer y Agnew, 1989); la Figura 1 ilustra estos mecanismos actuando en una sección de acuífero idealizado.…”
Section: Materials Y Métodosunclassified
“…La marea terrestre actúa directamente sobre la matriz de los materiales que conforman el acuífero, por lo que la respuesta del nivel del agua dentro de un pozo a la acción de la marea terrestre es controlada principalmente por las propiedades elásticas de la matriz porosa; mientras que, la presión barométrica actúa en la superficie libre del agua dentro del pozo y en la superficie del terreno de manera simultánea (Bredehoeft, 1967;Van Der Kamp y Gale, 1983;Rojstaczer y Agnew, 1989); la Figura 1 ilustra estos mecanismos actuando en una sección de acuífero idealizado.…”
Section: Materials Y Métodosunclassified
“…They note that including compressibility would lead to lower specific storage in general (the term 1 -K/K s would always be less than 1). Similar to the approach applied by Merritt (2004), this study uses the first form S s expression (Equation [D-1]) as given by Bredehoeft (1967).…”
Section: D11 Methodologymentioning
confidence: 99%
“…Bredehoeft (1967) showed that the fluctuations in head in an open well produced by tidal dilatation were a function of the specific storage of the aquifer. This analysis assumed incompressible grains, a simplifying assumption that was later relaxed by various authors.…”
Section: C13 Parameter Estimationmentioning
confidence: 99%
“…The reasons why we utilized the questionnaire survey of hot or mineral spring waters are as follows: 1) hot or mineral spring water is generally confined, and confined groundwater is much more sensitive to volumetric strain changes than unconfined groundwater (Bredehoeft, 1967); 2) hot or mineral spring water comes from deeper sources than normal groundwater; 3) hot or mineral spring water usually flows up along cracks in basement rock in a fault zone and brings some information about such zones, and 4) people in general, are more interested in hot or mineral spring water than normal groundwater and this should result in a higher volume of quality data on the survey. The number of reported groundwater anomalies was 56, while 186 springs reported no anomalies.…”
Section: Observation Site and Methodsmentioning
confidence: 99%